The Role of Gender (M/F) in the Workplace: The Case of Municipality of Athens, Greece - Papamichail, Stella; Karakosta, Argyro; Sklavou, Konstantina (International Journal of Gender Studies, 2024)
Purpose: This article presents the results of a survey conducted on employees of the municipality of Athens, Greece, in the context of an extensive survey on the implementation of the European Charter for Gender Equality in Local Communities and regarding stereotypes and discrimination between men and women in the specific survey population. Methodology: In particular, a survey was developed aimed to investigate the existence of stereotypical perceptions about gender within the Municipality and the absence of awareness of the need to integrate gender equality in all municipal policies. The survey was conducted between June and September 2023, online. A total of 258 employees in various Services and Organizations of the municipality of Athens participated in the survey, 71% women and 27% men, with an average age of 49 years old. The results of the research show that the gender of employees had a negative impact in the working life for women, confirming its role in inequalities and reduced opportunities for career development. Findings: The results also revealed that women in greater degree compared to men, have suffered a slowdown in their professional development due to their personal-family responsibilities, demonstrating that balancing work and family life is a difficult equation, especially for female employees. The study highlights persistent gender disparities, impacting work life balance and career progression for women. Unique Contribution to Theory, Practice and Policy: Its findings suggest a need for targeted policies that address gender-based barriers, promoting a more equitable work environment in municipal roles.